Effect of multi-walled carbon nanotube on thermal decomposition, mechanical and heat-induced shape memory properties of crosslinked poly(vinyl alcohol). (22nd October 2021) - Fan, Leiming; Mei, Xinliang; Zhang, Juan; Zhu, Jiaxing; Wang, Xingsheng; Li, Yanchun; Cai, Wei
Abstract: Shape memory polymers are attractive smart materials that have many promising applications in a wide variety of fields. Here the multi-walled carbon nanotube (MWCNT) was used to adjust the performance of crosslinked poly(vinyl alcohol) (PVA), which had acetal reaction with glutaraldehyde (GA). The thermal degradation, mechanical strength and shape recovery properties of PVA/MWCNT/GA membranes were investigated by thermogravimetry, differential scanning calorimetry, x-ray scattering, dynamic mechanical analysis, tensile test and thermal-stimulus shape memory recovery measurements. The MWCNT embedded in the crosslinked PVA matrix accelerated the breaking of C–O bonds. The mechanical strength and shape recovery properties of PVA/MWCNT/GA composites were tunable. As the MWCNT loading increase in crosslinked PVA matrix, the yield strength increased from 3.85 MPa to 10.21 MPa, breaking elongation decreased from 230% to 50%, the 100% shape recovery time decreased from 27 s to 16 s, respectively.